Dynamic behaviors and bandwidth-enhanced time-delay signature suppression of mutually coupled spin-polarized vertical-cavity surface-emitting lasers. (May 2022) - Liu, Bocheng; Xie, Yiyuan; Song, Tingting; Ye, Yichen; Jiang, Xiao; Chai, Junxiong; Tang, Qianfeng; Feng, Manying
Highlights: Dynamic behaviors of novel MCSP-VCSELs with its TDS and bandwidth are illustrated. Numerous nonlinear behaviors (S, PS, PD, PQ, PO, C states) have been observed. The period-doubling route to chaos is revealed. Simultaneously TDS suppression and bandwidth enhancement are implemented. Influence of laser crucial parameters are obtained with definitive conclusions. Abstract: A novel symmetric model based on the mutually coupled spin-polarized vertical-cavity surface-emitting lasers (MCSP-VCSELs) subject to optically pumped is implemented and analyzed in this paper. Numerous nonlinear dynamic behaviors containing the state of steady, period, period-doubling, and chaos have been observed in the bifurcation diagram, revealing the period-doubling route to chaos. The characteristics of these dynamic behaviors are analyzed in detail along with clarifying the physical mechanism of their occurrence. The influences of laser parameters on the dynamic behaviors are investigated through mapping diagrams, and the results show that both the pump intensity and pump ellipticity are crucial to the complicated dynamic behaviors including chaos. Additionally, the increase of the coupling strength, coupling time delay, and frequency detuning have beneficial impacts to chaos while the spin relaxation rate has a harmful effect on the contrary. The comparison results on different parameter planes illustrate that the time-delay signature (TDS) suppression and bandwidth enhancement can be achieved simultaneously when coupling strength, frequency detuning and pump strength are relatively large. Therefore, the MCSP-VCSELs have an application prospect in chaos-based fields.